Cooperation between developed and developing countries in promotion of 3R - Makiya, Kuniaki...[et al.] (2006)
Examines trends in international discussion and collaboration towards 3R (reduce, reuse, recycle) between developed and developing countries. Looks into policy barriers, gaps, and opportunities facing international cooperation towards sustainable production and consumption, with an emphasis on cooperation between developed and developing countries in the process of promoting and implementing viable 3R policies.